KETIMPANGAN DIGITAL DAN REPRODUKSI STRATIFIKASI SOSIAL: PERAN SEKOLAH DALAM MEMPERLEBAR ATAU MEMPERSEMPIT JURANG PENDIDIKAN DI ERA PASCA-PANDEMI - Mujahidin (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
The COVID-19 pandemic has accelerated the mass digitalisation of education; however, this transformation has actually exposed and exacerbated the deep-rooted structural inequalities within the Indonesian education system. This essay aims to critically examine the relationship between the digital divide and the reproduction of social stratification, as well as to analyse the ambivalent role of schools in widening or narrowing the educational divide in the post-pandemic era. Employing a literature review with a descriptive-analytical qualitative approach, this study integrates the perspectives of Pierre Bourdieu’s theory of social reproduction and contemporary digital divide theory to construct a coherent argument regarding the structural mechanisms of digital educational inequality. The analysis reveals that the digital divide operates as a mechanism for the reproduction of social stratification through the transformation of traditional cultural capital into digital cultural capital, whereby students from upper-middle-class backgrounds gain cumulative advantages from access to infrastructure, high levels of digital literacy, and adequate support ecosystems, whilst students from marginalised backgrounds experience digital exclusion that reinforces the cycle of structural poverty. Furthermore, schools play a dualistic role: on the one hand, they can narrow the gap through inclusive hybrid learning, affirmative digital literacy programmes, compensatory resource allocation policies, and digital justice pedagogy; on the other hand, they can widen inequalities through uncritical adoption of technology, class bias in pedagogical design, the commercialisation of online educational services, and assessment practices that assume an equality of access that does not exist in reality. This essay concludes that realising equitable education in the post-pandemic era requires a paradigm shift from a technocratic approach towards a holistic approach that integrates infrastructure, pedagogical capacity, affirmative policies, and the deconstruction of structural biases in the digitalisation of education.